Flexible circuit board cover film and preparation method thereof
Through photothermal dual curing technology, combined with UV light irradiation and hot pressing curing, a flexible circuit board covering film with high peeling force and acid resistance was prepared, which solved the problem of the covering film being undustable at high temperatures and achieved high peeling strength and acid resistance. sex.
Patent Information
- Application Number
- CN202411536539.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-10
AI Technical Summary
The existing flexible circuit board covering film is not durable at high temperatures, and has insufficient peeling performance and acid-base resistance. The prior art is difficult to meet these requirements simultaneously by increasing the hardness of the glue layer or designing a layered structure.
Using photothermal dual curing technology, a cross-linked structure is formed through acrylic prepolymers, benzoxazine-phenolic epoxy resins, photoinitiators and photosensitizer compositions, and combined with UV light irradiation and hot pressing curing, the cross-linked structure is prepared with High peeling force and acid resistance covering film.
The covering film does not reduce the peeling force at a high temperature of 288°C, and maintains good performance in an acidic environment. The peeling strength reaches 1.4N/mm, meeting the requirements of high weather resistance.
Smart Images

Figure BDA0005111684900000111 
Figure BDA0005111684900000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, in particular to a flexible circuit board covering film and a preparation method thereof. Background Art
[0002] With the development of electronic products, the application of flexible circuit boards is becoming more and more extensive, and cover film is a very important material for flexible circuit boards.
[0003] The cover film is applied to the outer surface of the flexible circuit board to prevent dust, resist soldering, and resist chemicals. It can also enhance the circuit board's resistance to flex and stress damage. After the cover film is attached to the flexible circuit board, it needs to undergo two reflow soldering processes. If the cover film is not resistant to high temperatures, bubbles will be generated during the second reflow soldering process, affecting the performance of the circuit board.
[0004] In the prior art, the traditional method for solving the problem of the covering film not being resistant to high temperatures is to increase the hardness of the glue layer in the covering film to make it more stable, but increasing the hardness will deteriorate the adhesion performance of the covering film and reduce the peeling performance; the prior art also adopts the following methods, such as CN111892881A-a method for preparing a high-temperature resistant and highly adhesive covering film or protective tape, which adopts acrylic glue or organic silica gel, adds any one or more reinforcing components of antioxidants, toughening agents, accelerators, curing agents, anti-aging agents, stabilizers, plasticizers, flame retardants, and ultraviolet light absorbers, adds the glue and the reinforcing components to the solvent in proportion, and mixes them evenly to prepare glue for the protective tape. Due to the coating / sputtering, pre-curing and post-curing processes adopted, the adhesive layer can be gradually cured to completely form a high-quality three-dimensional cross-linked network, thereby ensuring the cohesion and high adhesion, high temperature resistance and stability of the comprehensive performance of the adhesive layer; such as CN116751392A-A high-temperature resistant covering film and its preparation method, a high-temperature resistant covering film using (anti-corona) polyimide (PI) film combined with polyamideimide (PAI) varnish and surface sintered fluorine-based polymer, has excellent flatness, operability, dielectric strength, dielectric constant, insulation, colorization to form optical shielding and thermal stability, and can meet the working environment of 200°C or even above for a long time.
[0005] The above-mentioned prior art achieves the purpose of high temperature resistance of the covering film by increasing the hardness of the glue layer, adding reinforcing components to the glue, and designing the layered structure of the covering film. However, the prior art has not yet mentioned the preparation of flexible circuit board covering films by the light-heat dual curing technology path. This application aims to explore the use of this technology path to achieve high temperature resistance of the covering film while having high peeling force and acid and alkali resistance. Summary of the invention
[0006] In order to achieve high temperature resistance and high peeling force, acid and alkali resistance of the cover film, the present invention provides a flexible circuit board cover film prepared by a light-heat dual curing technology path and a preparation method thereof. The specific technical scheme of the present invention is as follows:
[0007] A flexible circuit board cover film can achieve light and heat dual curing, the cover film is composed of a release film, a light and heat dual curing composition, and a polyimide film from top to bottom, wherein the light and heat dual curing composition includes an acrylic prepolymer, a benzoxazine-phenolic epoxy resin, a photoinitiator, a photosensitizer, and a solvent;
[0008] Preferably, the photothermal dual curing composition comprises the following components: by mass, 80-125 parts of acrylic prepolymer, 8-25 parts of benzoxazine-phenolic epoxy resin, 0.1-10 parts of photoinitiator, 0.1-5 parts of photosensitizer, and 10-100 parts of solvent;
[0009] Preferably, the acrylic prepolymer comprises the following components, by weight: 50-80 parts of acrylic soft monomer, 25-50 parts of hard monomer, 3-15 parts of hydroxyl monomer, 0.5-5 parts of functional acrylic monomer, 0.1-0.6 parts of initiator, and 150-200 parts of solvent;
[0010] Further preferably, the acrylic soft monomer is one or more of butyl acrylate, ethyl acrylate, and isooctyl acrylate;
[0011] Further preferably, the hard monomer is one or more of methyl methacrylate, styrene, and acrylonitrile;
[0012] Further preferably, the hydroxyl monomer is one or more of acrylic acid, acrylamide, methacrylic acid, and glycidyl methacrylate;
[0013] Further preferably, the acrylic functional monomer is an acrylic monomer containing one or more of carboxyl, acyl, and acid anhydride groups;
[0014] Further preferably, the initiator is one or more of dibenzoyl peroxide, azobisisobutyronitrile, and azobisisoheptylnitrile;
[0015] More preferably, the second solvent is one or more of ethyl acetate, toluene, xylene, and butanone.
[0016] Preferably, the acrylic prepolymer is prepared as follows:
[0017] Mixing acrylic soft monomer, hard monomer, hydroxyl monomer and acrylic functional monomer to obtain a monomer mixture; taking half of the monomer mixture and mixing it with one-third of the solvent II, adding one-quarter of the initiator, mixing evenly, heating to 70-90° C. in a nitrogen atmosphere, and reacting for 1-3 hours to obtain a reaction liquid; mixing the remaining half of the monomer mixture, one-quarter of the initiator and one-third of the solvent II, slowly adding dropwise to the reaction liquid, reacting at 80-100° C. for 1-3 hours, adding one-quarter of the initiator, reacting at 70-90° C. for 1-3 hours, adding the remaining one-quarter of the initiator, reacting at 60-80° C. for 0.5-1 hour, keeping warm for 1-2 hours, and finally adding the remaining one-third of the solvent II to dilute to obtain an acrylic prepolymer;
[0018] Preferably, the glass transition temperature (Tg) of the acrylic prepolymer is -30°C to 10°C.
[0019] Preferably, the benzoxazine-phenolic epoxy resin is prepared by the following method:
[0020] The benzoxazine resin and the phenolic epoxy resin are melt-blended at 80°C according to a proportion, stirred for 20 minutes to make them uniformly mixed, and then cured according to a process of 140°C / 1h+150°C / 1h+160°C / 1h+170°C / 1h+180°C / 2h+200°C / 2h+220°C / 2h to obtain a benzoxazine-phenolic epoxy resin;
[0021] Further preferably, the molar ratio of the benzoxazine resin to the phenolic epoxy resin is: 0.2-4, for example, the molar ratio is 0.2, 0.4, 0.67, 0.8, 1.0, 1.5, 2, 2.5, 3, 3.5, 4, etc., and any value within the range of 0.2-4;
[0022] Further preferably, the benzoxazine resin is one or more of bisphenol A type benzoxazine resin, bisphenol F type benzoxazine resin, and MDA type benzoxazine resin;
[0023] Further preferably, the novolac epoxy resin is one or more of phenol-type novolac epoxy resin, o-cresol-type novolac epoxy resin, and bisphenol A-type novolac epoxy resin;
[0024] Preferably, the photoinitiator is one or more of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide, diaryl iodonium salt, triaryl sulfonium salt, and ferrocenium salt;
[0025] Preferably, the photosensitizer is one or more of condensed ring quinones, azo compounds, and organic sulfides;
[0026] Preferably, the solvent 1 is one or more of ethyl acetate, toluene, xylene and butanone.
[0027] A method for preparing a high temperature resistant flexible circuit board cover film comprises the following steps:
[0028] 1. Preparation of acrylic prepolymer:
[0029] Mix acrylic soft monomer, hard monomer, hydroxyl monomer and acrylic functional monomer to obtain a monomer mixture; take half of the monomer mixture and mix it with one-third of the solvent II, add one-quarter of the initiator, mix well, protect under nitrogen atmosphere, heat to 70-90°C, react for 1-3h, and obtain a reaction liquid; mix the remaining half of the monomer mixture, one-quarter of the initiator and one-third of the solvent II, slowly add dropwise to the reaction liquid, react at 80-100°C for 1-3h, add one-quarter of the initiator, react at 70-90°C for 1-3h, add the remaining one-quarter of the initiator, react at 60-80°C for 0.5-1h, keep warm for 1-2h, and finally add the remaining one-third of the solvent II to dilute, and obtain an acrylic prepolymer.
[0030] 2. Preparation of benzoxazine-phenolic epoxy resin:
[0031] The benzoxazine resin and the phenolic epoxy resin are melt-blended at 80°C according to a proportion, stirred for 20 minutes to make them uniformly mixed, and then cured according to a process of 140°C / 1h+150°C / 1h+160°C / 1h+170°C / 1h+180°C / 2h+200°C / 2h+220°C / 2h to obtain a benzoxazine-phenolic epoxy resin;
[0032] 3. Preparation of light-heat dual-curing composition:
[0033] The acrylic prepolymer, benzoxazine-phenolic epoxy resin, photoinitiator, photosensitizer and solvent are uniformly mixed to obtain a light-heat dual curing composition;
[0034] 4. Preparation of a flexible circuit board cover film:
[0035] The light-heat dual-curing composition is coated on the polyimide film, and after being dried in an oven, an adhesive film is formed, and a layer of release film is covered on the surface of the adhesive film to obtain a single-sided release covering film.
[0036] A method for using a flexible circuit board cover film: when using, tear off the release film, place it under a UV light source for irradiation activation, and then stick it on the circuit board, press it for 30-300s at a temperature of 120-180°C and a pressure of 20-100kg to complete the process;
[0037] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0038] 1. The present invention designs and synthesizes a benzoxazine-phenolic epoxy resin, which is applied to a flexible circuit board cover film. The introduction of benzoxazine further improves the heat resistance of the phenolic epoxy resin, improves the stability of the product, makes the cover film acid-resistant, and does not reduce the peeling force after being subjected to a high temperature tin furnace at 288°C.
[0039] 2. The present invention provides a flexible circuit board covering film, the adhesive layer of the covering film is a light-heat dual-curing composition. When in use, the covering film is firstly irradiated with UV light, and the photoinitiator interacts with the benzoxazine-phenolic epoxy resin and the acrylic prepolymer to form a certain cross-linking structure, and then pressed at 120-180°C and 20-100kg pressure. During the hot pressing process, the aldehyde-formaldehyde group is thermally cured to further enhance the cross-linking strength, so that the peel strength of the covering film after light curing and thermal curing reaches 1.4N / mm.
[0040] 3. By controlling the glass transition temperature of acrylic prepolymer, the requirements of high peel strength and high weather resistance of the covering film can be met at the same time, so that all aspects of the performance of the covering film can reach a balanced state. DETAILED DESCRIPTION
[0041] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in conjunction with specific embodiments.
[0042] The endpoints and any values of the ranges disclosed in this disclosure are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this disclosure.
[0043] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.
[0044] In the following examples, the raw materials used are shown in the following table:
[0045] name illustrate Manufacturer CB3100 Bisphenol A benzoxazine resin Keyi Polymer SQPN-051 Phenol novolac epoxy resin Shandong Holy Spring EPON 828 Bisphenol A epoxy resin Hanson ITX Photosensitizer, 2-isopropylthioxanthone TCI MMA Hard monomer: methyl methacrylate Huayi BA Acrylic soft monomer: Butyl acrylate Huayi AA Hydroxyl monomer: acrylic acid Buffs AAM Functional monomer: acrylamide Maclean EA Ethyl acetate Aladdin AIBN Azobisisobutyronitrile initiator TCl GR-SS059 Photoinitiator, triarylsulfonium hexafluoroantimonate Gurun Technology
[0046] The preparation of benzoxazine-phenolic epoxy resin includes the following three synthesis examples:
[0047] Synthesis Example 1: Bisphenol A type benzoxazine resin and phenol type novolac epoxy resin are melt-blended at a molar ratio of 6:4 at 80°C, stirred for 20 minutes to mix evenly, and then cured according to a process of 140°C / 1h+150°C / 1h+160°C / 1h+170°C / 1h+180°C / 2h+200°C / 2h+220°C / 2h to obtain benzoxazine-novolac epoxy resin.
[0048] Synthesis Example 2: Bisphenol A type benzoxazine resin and phenol type novolac epoxy resin are melt-blended at 80°C in a molar ratio of 4:6, stirred for 20 minutes to mix evenly, and then cured according to a process of 140°C / 1h+150°C / 1h+160°C / 1h+170°C / 1h+180°C / 2h+200°C / 2h+220°C / 2h to obtain benzoxazine-novolac epoxy resin.
[0049] Synthesis Example 3: Bisphenol A type benzoxazine resin and bisphenol A type epoxy resin are melt-blended at a molar ratio of 6:4 at 80°C, stirred for 20 minutes to mix evenly, and then cured according to a process of 140°C / 1h+150°C / 1h+160°C / 1h+170°C / 1h+180°C / 2h+200°C / 2h+220°C / 2h to obtain benzoxazine-epoxy resin.
[0050] The preparation of acrylic prepolymers includes the following five synthesis examples:
[0051] Synthesis Example 4: 60 parts of BA, 40 parts of MMA, 5 parts of AA, and 1 part of AAM are mixed uniformly to obtain a monomer mixture; half of the monomer mixture by mass is mixed with 60 parts of ethyl acetate, 0.1 parts of AIBN are added, and after mixing uniformly, the mixture is heated to 70-90°C under nitrogen atmosphere protection, and reacted for 1-3 hours to obtain a reaction liquid; the remaining half of the monomer mixture by mass, 0.1 parts of AIBN and 60 parts of ethyl acetate are mixed, and the mixture is slowly added dropwise to the reaction liquid, reacted at 80-100°C for 1-3 hours, 0.1 parts of AIBN are added, and the mixture is reacted at 70-90°C for 1-3 hours, 0.1 parts of AIBN are added, and the mixture is reacted at 60-80°C for 0.5-1 hours, and the mixture is kept warm for 1-2 hours, and finally 60 parts of ethyl acetate are added to dilute the mixture to obtain an acrylic prepolymer with a solid content of 37% and a glass transition temperature of -5°C.
[0052] Synthesis Example 5: 67 parts of BA, 33 parts of MMA, 5 parts of AA and 1 part of AAM are mixed uniformly to obtain a monomer mixture; half of the monomer mixture by mass is mixed with 60 parts of ethyl acetate, 0.1 parts of AIBN are added, and after mixing uniformly, the mixture is heated to 70-90°C under nitrogen atmosphere protection, and reacted for 1-3 hours to obtain a reaction liquid; the remaining half of the monomer mixture by mass, 0.1 parts of AIBN and 60 parts of ethyl acetate are mixed, and the mixture is slowly added dropwise to the reaction liquid, reacted at 80-100°C for 1-3 hours, 0.1 parts of AIBN are added, and the mixture is reacted at 70-90°C for 1-3 hours, 0.1 parts of AIBN are added, and the mixture is reacted at 60-80°C for 0.5-1 hours, and the mixture is kept warm for 1-2 hours, and finally 60 parts of ethyl acetate are added to dilute the mixture to obtain an acrylic prepolymer having a solid content of 37% and a glass transition temperature of -15°C.
[0053] Synthesis Example 6: 52 parts of BA, 48 parts of MMA, 5 parts of AA and 1 part of AAM are mixed uniformly to obtain a monomer mixture; half of the monomer mixture by mass is mixed with 60 parts of ethyl acetate, 0.1 parts of AIBN are added, and after mixing uniformly, the mixture is heated to 70-90°C under nitrogen atmosphere protection, and reacted for 1-3 hours to obtain a reaction liquid; the remaining half of the monomer mixture by mass, 0.1 parts of AIBN and 60 parts of ethyl acetate are mixed, and the mixture is slowly added dropwise to the reaction liquid, reacted at 80-100°C for 1-3 hours, 0.1 parts of AIBN are added, and the mixture is reacted at 70-90°C for 1-3 hours, 0.1 parts of AIBN are added, and the mixture is reacted at 60-80°C for 0.5-1 hours, and the mixture is kept warm for 1-2 hours, and finally 60 parts of ethyl acetate are added to dilute the mixture to obtain an acrylic prepolymer having a solid content of 37% and a glass transition temperature of 5°C.
[0054] Synthesis Example 7: 85 parts of BA, 15 parts of MMA, 5 parts of AA and 1 part of AAM are mixed uniformly to obtain a monomer mixture; half of the monomer mixture by mass is mixed with 60 parts of ethyl acetate, 0.1 parts of AIBN are added, and after mixing uniformly, the mixture is heated to 70-90% under nitrogen atmosphere protection, and reacted for 1-3 hours to obtain a reaction liquid; the remaining half of the monomer mixture by mass, 0.1 parts of AIBN and 60 parts of ethyl acetate are mixed, and the mixture is slowly added dropwise to the reaction liquid, reacted at 80-100°C for 1-3 hours, 0.1 parts of AIBN are added, and the mixture is reacted at 70-90°C for 1-3 hours, 0.1 parts of AIBN are added, and the mixture is reacted at 60-80°C for 0.5-1 hours, and the mixture is kept warm for 1-2 hours, and finally 60 parts of ethyl acetate are added to dilute the mixture to obtain an acrylic prepolymer having a solid content of 37% and a glass transition temperature of -35°C.
[0055] Synthesis Example 8: 45 parts of BA, 55 parts of MMA, 5 parts of AA and 1 part of AAM are mixed uniformly to obtain a monomer mixture; half of the monomer mixture by mass is mixed with 60 parts of ethyl acetate, 0.1 parts of AIBN are added, and after mixing uniformly, the mixture is heated to 70-90°C under nitrogen atmosphere protection, and reacted for 1-3 hours to obtain a reaction liquid; the remaining half of the monomer mixture by mass, 0.1 parts of AIBN and 60 parts of ethyl acetate are mixed, and the mixture is slowly added dropwise to the reaction liquid, reacted at 80-100°C for 1-3 hours, 0.1 parts of AIBN are added, and the mixture is reacted at 70-90°C for 1-3 hours, 0.1 parts of AIBN are added, and the mixture is reacted at 60-80°C for 0.5-1 hours, and the mixture is kept warm for 1-2 hours, and finally 60 parts of ethyl acetate are added to dilute the mixture to obtain an acrylic prepolymer with a solid content of 37% and a glass transition temperature of 15°C.
[0056] The present invention is further understood through Examples 1-6 and Comparative Examples 1-6.
[0057] Example 1: 100 parts of the acrylic prepolymer (Tg = -5°C) of Synthesis Example 4, 20 parts of the benzoxazine-phenolic epoxy resin of Synthesis Example 1, 0.5 parts of triaryl hexafluoroantimonate sulfonium salt, 0.15 parts of ITX, and 25 parts of ethyl acetate were mixed uniformly to obtain a light-heat dual-curing composition;
[0058] The photothermal dual curing composition was coated on a polyimide film with a thickness of 50 μm, and dried at 110° C. for 3 min. The dry film thickness was 50 μm. After drying, another layer of release film with a thickness of 30 μm was covered on the surface of the film to obtain a film.
[0059] When using, remove the release film and place it under UV light with a wavelength of 365nm for activation. The activation energy is 2000mJ / cm 2 Then it was attached to the circuit board and pressed for 100s at 160°C and 70kg pressure to test the peeling force.
[0060] Example 2: 80 parts of the acrylic prepolymer (Tg = -5°C) of Synthesis Example 4, 8 parts of the benzoxazine-phenolic epoxy resin of Synthesis Example 2, 0.5 parts of triaryl hexafluoroantimonate sulfonium salt, 0.15 parts of ITX, and 25 parts of ethyl acetate were mixed uniformly to obtain a light-heat dual-curing composition;
[0061] The photothermal dual curing composition was coated on a polyimide film with a thickness of 50 μm, and dried at 110° C. for 3 min. The dry film thickness was 50 μm. After drying, another layer of release film with a thickness of 30 μm was covered on the surface of the film to obtain a film.
[0062] When using, remove the release film and place it under UV light with a wavelength of 365nm for activation. The activation energy is 2000mJ / cm 2Then it was attached to the circuit board and pressed for 100s at 160°C and 70kg pressure to test the peeling force.
[0063] Example 3: 100 parts of the acrylic prepolymer (Tg = -15 ° C) of Synthesis Example 5, 20 parts of the benzoxazine-phenolic epoxy resin of Synthesis Example 1, 0.5 parts of triaryl hexafluoroantimonate sulfonium salt, 0.15 parts of ITX, and 25 parts of ethyl acetate were mixed uniformly to obtain a light-heat dual-curing composition;
[0064] The photothermal dual curing composition was coated on a polyimide film with a thickness of 50 μm, and dried at 110° C. for 3 min. The dry film thickness was 50 μm. After drying, another layer of release film with a thickness of 30 μm was covered on the surface of the film to obtain a film.
[0065] When using, remove the release film and place it under UV light with a wavelength of 365nm for activation. The activation energy is 2000mJ / cm 2 Then it was attached to the circuit board and pressed for 100s at 160°C and 70kg pressure to test the peeling force.
[0066] Example 4: 125 parts of the acrylic prepolymer (Tg = -15 ° C) of Synthesis Example 5, 25 parts of the benzoxazine-phenolic epoxy resin of Synthesis Example 2, 0.5 parts of triaryl hexafluoroantimonate sulfonium salt, 0.15 parts of ITX, and 25 parts of ethyl acetate were mixed to obtain a light-heat dual-curing composition;
[0067] The photothermal dual curing composition was coated on a polyimide film with a thickness of 50 μm, and dried at 110° C. for 3 min. The dry film thickness was 50 μm. After drying, another layer of release film with a thickness of 30 μm was covered on the surface of the film to obtain a film.
[0068] When using, remove the release film and place it under UV light with a wavelength of 365nm for activation. The activation energy is 2000mJ / cm 2 Then it was attached to the circuit board and pressed for 100s at 160°C and 70kg pressure to test the peeling force.
[0069] Example 5: 100 parts of the acrylic prepolymer (Tg = 5°C) of Synthesis Example 6, 20 parts of the benzoxazine-phenolic epoxy resin of Synthesis Example 1, 0.5 parts of triaryl hexafluoroantimonate sulfonium salt, 0.15 parts of ITX, and 25 parts of ethyl acetate were mixed uniformly to obtain a light-heat dual-curing composition;
[0070] The photothermal dual curing composition was coated on a polyimide film with a thickness of 50 μm, and dried at 110° C. for 3 min. The dry film thickness was 50 μm. After drying, another layer of release film with a thickness of 30 μm was covered on the surface of the film to obtain a film.
[0071] When using, remove the release film and place it under UV light with a wavelength of 365nm for activation. The activation energy is 2000mJ / cm 2 Then it was attached to the circuit board and pressed for 100s at 160°C and 70kg pressure to test the peeling force.
[0072] Example 6: 90 parts of the acrylic prepolymer (Tg = 5°C) of Synthesis Example 6, 15 parts of the benzoxazine-phenolic epoxy resin of Synthesis Example 2, 0.5 parts of triaryl hexafluoroantimonate sulfonium salt, 0.15 parts of ITX, and 25 parts of ethyl acetate were mixed uniformly to obtain a light-heat dual-curing composition;
[0073] The photothermal dual curing composition was coated on a polyimide film with a thickness of 50 μm, and dried at 110° C. for 3 min. The dry film thickness was 50 μm. After drying, another layer of release film with a thickness of 30 μm was covered on the surface of the film to obtain a film.
[0074] When using, remove the release film and place it under UV light with a wavelength of 365nm for activation. The activation energy is 2000mJ / cm 2 Then it was attached to the circuit board and pressed for 100s at 160°C and 70kg pressure to test the peeling force.
[0075] Comparative Example 1: 100 parts of the acrylic prepolymer (Tg = -5°C) of Synthesis Example 4, 20 parts of phenol-type novolac epoxy resin, 0.5 parts of triaryl hexafluoroantimonate sulfonium salt, 0.15 parts of ITX, and 25 parts of ethyl acetate were mixed uniformly to obtain a light-heat dual-curing composition;
[0076] The photothermal dual curing composition was coated on a polyimide film with a thickness of 50 μm, and dried at 110° C. for 3 min. The dry film thickness was 50 μm. After drying, another layer of release film with a thickness of 30 μm was covered on the surface of the film to obtain a film.
[0077] When using, remove the release film and place it under UV light with a wavelength of 365nm for activation. The activation energy is 2000mJ / cm 2 Then it was attached to the circuit board and pressed for 100s at 160°C and 70kg pressure to test the peeling force.
[0078] Comparative Example 2: 100 parts of the acrylic prepolymer (Tg = -5°C) of Synthesis Example 4, 20 parts of the benzoxazine-epoxy resin of Synthesis Example 3, 0.5 parts of triaryl hexafluoroantimonate sulfonium salt, 0.15 parts of ITX, and 25 parts of ethyl acetate were mixed uniformly to obtain a light-heat dual-curing composition;
[0079] The photothermal dual curing composition was coated on a polyimide film with a thickness of 50 μm, and dried at 110° C. for 3 min. The dry film thickness was 50 μm. After drying, another layer of release film with a thickness of 30 μm was covered on the surface of the film to obtain a film.
[0080] When using, remove the release film and place it under UV light with a wavelength of 365nm for activation. The activation energy is 2000mJ / cm 2 Then it was attached to the circuit board and pressed for 100s at 160°C and 70kg pressure to test the peeling force.
[0081] Comparative Example 3: 100 parts of the acrylic prepolymer (Tg = -35°C) of Synthesis Example 7, 20 parts of the benzoxazine-phenolic epoxy resin of Synthesis Example 1, 0.5 parts of triaryl hexafluoroantimonate sulfonium salt, 0.15 parts of ITX, and 25 parts of ethyl acetate were mixed uniformly to obtain a light-heat dual-curing composition;
[0082] The photothermal dual curing composition was coated on a polyimide film with a thickness of 50 μm, and dried at 110° C. for 3 min. The dry film thickness was 50 μm. After drying, another layer of release film with a thickness of 30 μm was covered on the surface of the film to obtain a film.
[0083] When using, remove the release film and place it under UV light with a wavelength of 365nm for activation. The activation energy is 2000mJ / cm 2 Then it was attached to the circuit board and pressed for 100s at 160°C and 70kg pressure to test the peeling force.
[0084] Comparative Example 4: 100 parts of the acrylic prepolymer (Tg = 15°C) of Synthesis Example 8, 20 parts of the benzoxazine-phenolic epoxy resin of Synthesis Example 1, 0.5 parts of triaryl hexafluoroantimonate sulfonium salt, 0.15 parts of ITX, and 25 parts of ethyl acetate were mixed uniformly to obtain a light-heat dual-curing composition;
[0085] The photothermal dual curing composition was coated on a polyimide film with a thickness of 50 μm, and dried at 110° C. for 3 min. The dry film thickness was 50 μm. After drying, another layer of release film with a thickness of 30 μm was covered on the surface of the film to obtain a film.
[0086] When using, remove the release film and place it under UV light with a wavelength of 365nm for activation. The activation energy is 2000mJ / cm 2 Then it was attached to the circuit board and pressed for 100s at 160°C and 70kg pressure to test the peeling force.
[0087] Comparative Example 5: 100 parts of the acrylic prepolymer (Tg = -5°C) of Synthesis Example 4, 20 parts of the benzoxazine-phenolic epoxy resin of Synthesis Example 1, 0.5 parts of triaryl hexafluoroantimonate sulfonium salt, 0.15 parts of ITX, and 25 parts of ethyl acetate were mixed uniformly to obtain a light-heat dual-curing composition;
[0088] The photothermal dual curing composition was coated on a polyimide film with a thickness of 50 μm, and dried at 110° C. for 3 min. The dry film thickness was 50 μm. After drying, another layer of release film with a thickness of 30 μm was covered on the surface of the film to obtain a film.
[0089] When using, tear off the release film, stick it on the circuit board, press it for 100s at a temperature of 160℃ and a pressure of 70kg to test the peeling force.
[0090] Comparative Example 6: 100 parts of the acrylic prepolymer (Tg = -5°C) of Synthesis Example 4, 20 parts of the benzoxazine-phenolic epoxy resin of Synthesis Example 1, 0.5 parts of triaryl hexafluoroantimonate sulfonium salt, 0.15 parts of ITX, and 25 parts of ethyl acetate were mixed uniformly to obtain a light-heat dual-curing composition;
[0091] The photothermal dual curing composition was coated on a polyimide film with a thickness of 50 μm, and dried at 110° C. for 3 min. The dry film thickness was 50 μm. After drying, another layer of release film with a thickness of 30 μm was covered on the surface of the film to obtain a film.
[0092] When using, remove the release film and place it under UV light with a wavelength of 365nm for activation. The activation energy is 2000mJ / cm 2 Then it was attached to the circuit board and pressed for 100s at 50°C and 5kg pressure to test the peeling force.
[0093] Test: The products prepared from Examples 1 to 6 and Comparative Examples 1 to 6 were subjected to performance tests, and the obtained data are shown below:
[0094] The initial peel force of the tape was tested according to ASTM D3330, as follows: Wipe the FPC circuit board with ethanol three times before testing. Cut the film into 1 cm wide strips, peel off the release film, stick it on an FPC circuit board, and roll it twice with a force of 2 kg. Before the peel test, place the adhesive in a controlled environment room (23°C / 50% relative humidity) for 30 minutes and use an Instron tensile tester to test it at a speed of 300 mm / min. Repeat each test three times and take the average value in N / mm.
[0095] Test the peel strength of the tape after UV+heat pressing according to ASTMD3330, as follows:
[0096] Wipe the FPC circuit board with ethanol three times before testing. Cut the film into 1cm wide strips and irradiate with UV (Fusion D lamp, UVA is about 1500mJ / cm 2 ), peel off the release film, stick it on an FPC circuit board, and press it for 100s at a temperature of 160°C and a pressure of 70kg. Before the peel test, the glue was placed in a controlled environment room (23°C / 50% relative humidity) for 24 hours and tested using an Instron tensile tester at a speed of 300mm / min. Each test was repeated three times and the average value was taken in N / mm.
[0097] The peeling force of the tape after acid immersion was tested according to ASTM D3330, as follows:
[0098] Wipe the FPC circuit board with ethanol three times before testing. Cut the film into 1cm wide strips and irradiate with UV (Fusion D lamp, UVA is about 1500mJ / cm 2 ), peel off the release film, stick it on an FPC circuit board, press it for 100s at 160℃ and 70kg pressure, and place the film in a controlled environment room (23℃ / 50% relative humidity) for 24 hours. Then put the sample in 5% hydrochloric acid solution, keep it in a 60℃ environment for 30min, take it out and place it in a controlled environment room for 2 hours to return to temperature, and use Instron's tensile testing machine for testing at a speed of 300mm / min. Each test is repeated three times and the average value is N / mm.
[0099] The peeling force of the tape after tinning furnace was tested according to ASTMD3330, as follows:
[0100] Wipe the FPC circuit board with ethanol three times before testing. Cut the film into 1cm wide strips and irradiate with UV (Fusion D lamp, UVA is about 1500mJ / cm 2 ), peel off the release film, stick it on an FPC circuit board, press it for 100s at a temperature of 160℃ and a pressure of 70kg, and place the glue in a controlled environment room (23℃ / 50% relative humidity) for 24 hours. Then place the sample in a tin furnace at 288℃ for 10s, repeat three times, and place it in a controlled environment room for 2 hours to return to temperature. Use Instron's tensile testing machine for testing at a speed of 300mm / min. Each test is repeated three times and the average value is taken in N / mm.
[0101] The test results are shown in the table below:
[0102]
[0103]
[0104] Conclusion: It can be seen from the data in the table that the phenolic epoxy resin in Comparative Example 1 is not modified with benzoxazine, which makes the film have poor acid resistance and heat resistance; the epoxy resin in Comparative Example 2 has no phenolic group, so the degree of thermal curing of the film is reduced; the acrylic prepolymer Tg in Comparative Example 3 and Comparative Example 4 is too low and too high, which will cause the peel strength of the film to decrease after curing; the film in Comparative Example 5 is not irradiated with a UV light source when in use, resulting in a decrease in the degree of cross-linking of the film after curing; the temperature and pressure of the hot pressing of the film in Comparative Example 6 are too low when in use, resulting in incomplete thermal activation of the film and a decrease in peel strength; Examples 1 to 6 prepared according to the method provided by the present invention have good peel strength, and excellent acid resistance and heat resistance.
[0105] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A flexible circuit board cover film, characterized in that: The covering film is composed of a release film, a light-heat dual-curing composition, and a polyimide film from top to bottom; The photothermal dual-curing composition comprises the following components: 80-125 parts of acrylic prepolymer, 8-25 parts of benzoxazine-phenolic epoxy resin, 0.1-10 parts of photoinitiator, 0.1-5 parts of photosensitizer, and 10-100 parts of solvent.
2. A flexible circuit board cover film according to claim 1, characterized in that: The acrylic prepolymer comprises the following components, calculated by weight: 50-80 parts of acrylic soft monomer, 25-50 parts of hard monomer, 3-15 parts of hydroxyl monomer, 0.5-5 parts of acrylic functional monomer, 0.1-0.6 parts of initiator, and 150-200 parts of solvent.
3. A flexible circuit board cover film according to claim 2, characterized in that: The acrylic soft monomer is one or more of butyl acrylate, ethyl acrylate, and isooctyl acrylate; the hard monomer is one or more of methyl methacrylate, styrene, and acrylonitrile; the hydroxyl monomer is one or more of acrylic acid, acrylamide, methacrylic acid, and glycidyl methacrylate; the acrylic functional monomer is an acrylic monomer containing one or more of carboxyl, acyl, and acid anhydride groups; the initiator is one or more of dibenzoyl peroxide, azobisisobutyronitrile, and azobisisoheptylnitrile.
4. A flexible circuit board cover film according to any one of claims 1 to 3, characterized in that: The acrylic prepolymer is prepared as follows: acrylic soft monomer, hard monomer, hydroxyl monomer and acrylic functional monomer are mixed to obtain a monomer mixture; half of the monomer mixture is mixed with one-third of the solvent II by weight, one-quarter of the initiator by weight is added, and after mixing evenly, the mixture is heated to 70-90° C. in a nitrogen atmosphere for reaction for 1-3 hours to obtain a reaction liquid; the remaining half of the monomer mixture, one-quarter of the initiator and one-third of the solvent II are mixed, and the mixture is slowly added dropwise to the reaction liquid, and the mixture is reacted at 80-100° C. for 1-3 hours, one-quarter of the initiator by weight is added, and the mixture is reacted at 70-90° C. for 1-3 hours, the remaining one-quarter of the initiator is added, and the mixture is reacted at 60-80° C. for 0.5-1 hours, and the mixture is kept warm for 1-2 hours, and finally the remaining one-third of the solvent II is added for dilution to obtain an acrylic prepolymer.
5. A flexible circuit board cover film according to any one of claims 1 to 4, characterized in that: The glass transition temperature (Tg) of the acrylic prepolymer is -30 to 10°C.
6. The flexible circuit board cover film according to claim 1, characterized in that: The preparation method of the benzoxazine-phenolic epoxy resin is as follows: melt-blending the benzoxazine resin and the phenolic epoxy resin according to a proportion at 80°C, stirring for 20 minutes to mix them evenly, and then curing them according to a process of 140°C / 1h+150°C / 1h+160°C / 1h+170°C / 1h+180°C / 2h+200°C / 2h+220°C / 2h to obtain the benzoxazine-phenolic epoxy resin.
7. A flexible circuit board cover film according to claim 6, characterized in that: The molar ratio of the benzoxazine resin to the phenolic epoxy resin is 0.2-4.
8. The flexible circuit board cover film according to claim 1, characterized in that: The photoinitiator is one or more of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide, diaryl iodonium salt, triaryl sulfonium salt, and ferrocenium salt; the photosensitizer is one or more of condensed ring quinones, azo compounds, and organic sulfides.
9. The flexible circuit board cover film according to claim 1, characterized in that: The photothermal dual curing composition can be activated by UV light, and the activation energy is 500-10000mJ / cm 2 .
10. A method for preparing a flexible circuit board cover film, characterized in that: The light-heat dual-curing composition is coated on the polyimide film, and after being dried in an oven, a release film is covered on the surface of the film to obtain a single-sided release covering film.
11. A method for using a flexible circuit board cover film, characterized in that: When using, tear off the release film, place it under a UV light source for activation, and then stick it on the circuit board. Press it for 30-300s at a temperature of 120-180℃ and a pressure of 20-100kg to complete the process.
12. A flexible circuit board, characterized in that: The flexible circuit board comprises the cover film according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of high-temperature-resistant high-persistent-adhesivity cover film or protective adhesive tape
CN111892881A
High-temperature-resistant cover film and preparation method thereof
CN116751392A
Cited By
Flexible printed circuit board and processing technology thereof
CN119997390A